The Mediating Role of Adoption QR-Code E-Wallets on User Behaviour - Sieradianto Angelia, Dinda Ayu; Indah Ramadhani, Ananda Fadia; Fanydia Ningsih, Nikken Nur (Jurnal Masyarakat Maritim, 2024)
Life continues to evolve in a more modern direction along with technological advancements. Digital transformation plays a crucial role in influencing consumer behavior and societal habits. In Indonesia, the financial sector leads in technological development, particularly in payment methods. In response to this growth, Bank Indonesia has introduced a policy to implement a single QR code that can be used across various payment applications, known as the Quick Response Indonesian Standard (QRIS). One of the benefits of non-cash payment technology is improving the payment ecosystem and enhancing payment service efficiency across sectors. The objective of this study is to examine the mediating role of QR-Code E-Wallets on User Behavior. This research utilizes SmartPLS version 3.2 as an analytical tool, with SEM methodology and a quantitative survey technique. The findings indicate that performance expectancy, social influence, and hedonic motivation significantly influence QR-wallet intention. Additionally, perceived expectancy and social influence positively and significantly impact Use Behavior, while hedonic motivation has a positive but not significant effect on Use Behavior. Furthermore, QR-Wallet intention can mediate the influence of hedonic motivation, performance expectancy, and social influence on Use Behavior.